Differentiated development patterns in Barroso: searching for specific intervention methods - Cristovao A.; Oostindie H.; Pereira F. (Strengthening endogenous development patterns in European agriculture, 1993)
This paper presents some results of an inquiry into the diversity of farming practices in Barroso. This diversity in farming styles is analysed as an outcome of complex socioeconomic processes and of the differentiated responses of farmers to recent policy interventions. The empirical diversity in styles of farming reflects an important difference in underlying development patterns, some styles being grounded in endogenous patterns whilst others clearly express more erogenous forms of development. From this fundamental difference it will be derived some suggestions on new forms of intervention which might contribute to the strengthening of endogenous development.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)